2001
DOI: 10.1210/jcem.86.9.7877
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Effect of Glucagon-Like Peptide-1 (7–36) Amide on Ad Libitum Energy Intake in Humans

Abstract: Seven studies have now been published pertaining to the acute effect of iv administration of glucagon-like peptide-1 (7-36) amide on ad libitum energy intake. In four of these studies energy intake was significantly reduced following the glucagon-like peptide-1 infusion compared with saline. In the remaining studies, no significant effect of glucagon-like peptide-1 could be shown. Lack of statistical power or low glucagon-like peptide-1 infusion rate may explain these conflicting results. Our aim was to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
162
1
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(188 citation statements)
references
References 20 publications
8
162
1
7
Order By: Relevance
“…Nine It is reasonable that the treatment-related body weight loss can rather be attributed to a decrease in energy intake. [69][70][71][72]. In a meta-analysis of studies in humans evaluating acute effects of GLP-1 infusion on food intake, a mean decrease of 11.7 % in the amount of ad libitum energy intake compared with saline [71] was reported.…”
Section: Glp-1 and Body Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine It is reasonable that the treatment-related body weight loss can rather be attributed to a decrease in energy intake. [69][70][71][72]. In a meta-analysis of studies in humans evaluating acute effects of GLP-1 infusion on food intake, a mean decrease of 11.7 % in the amount of ad libitum energy intake compared with saline [71] was reported.…”
Section: Glp-1 and Body Weightmentioning
confidence: 99%
“…[69][70][71][72]. In a meta-analysis of studies in humans evaluating acute effects of GLP-1 infusion on food intake, a mean decrease of 11.7 % in the amount of ad libitum energy intake compared with saline [71] was reported. GLP-1 receptors are expressed in vagal afferent neurons and total subdiaphragmatic or specific afferent vagotomy has been demonstrated to significantly attenuate the satiety effects of intraperitoneally administered GLP-1 [73].…”
Section: Glp-1 and Body Weightmentioning
confidence: 99%
“…Besides appetite control, GPR119 is also highly expressed in pancreatic β cells and involved in glucose-dependent insulin secretion as well as secretion of gastrointestinal incretin hormone and peptides (glucagon-like peptide-1 (GLP-1) [57] and GIP (glucose-dependent insulinotropic peptide) from enteroendocrine cells [57] (Figure 1). GLP-1 has, among other properties, insulinotropic effects inhibition of gastric emptying, reduction of appetite and promotion of satiety in humans [58] and rodents [59]. Likewise other FAs and FFAs receptors such as GPR120 [60] and FFA1 [61], GPR119 is a lipid sensing receptor [62] that is activated by oleic acid-containing lipids (e.g., N-oleoyl-dopamine) and regarded as a potential drug target for the treatment of T2D.…”
Section: Obesity Culprit Of Health Life In Westernized Societies: Diementioning
confidence: 99%
“…confirmed that GLP‐1 reduces food intake in a dose‐dependent manner in lean and overweight subjects (Verdich et al . ). Importantly, GLP‐1 retains its anorectic effects during chronic exposure.…”
Section: Introductionmentioning
confidence: 97%